The Mobilizing Effects of Economic Threats and Resources on the Formation of Local Occupy Wall Street Protest Groups in 2011. (August 2019) - Gillham, Patrick F.; Lindstedt, Nathan C.; Edwards, Bob; Johnson, Erik W.
This paper examines how threatening economic conditions and preexisting community resources facilitated the spread of Occupy Wall Street protest groups to more than 600 counties in the continental United States in 2011. Using a generalized linear mixed model, we find that economic threats and accessible resources are complementary facilitators of movement mobilization. But contrary to the expectations based on earlier media and scholarly accounts, the "disruptive threats" caused by the Great Recession failed to predict the formation of Occupy groups. Instead, groups were more likely to mobilize in counties that had the "positional threats" of relatively higher income inequality and relatively lower median incomes in comparison to state norms. However, the effect of positional economic threats was nuanced as counties with lower than average unemployment more likely had groups mobilized. In addition, resources continue to demonstrate empirical importance in explanations of social movement mobilization, as Occupy groups were more likely to form in counties with greater access to social-organizational and human resources. Combined, these findings suggest that scholars can strengthen their analyses by considering threats and resources as complementary facilitators of local protest mobilization and by focusing greater attention on how differing types of threats may influence the mobilization of social movements.